2018
DOI: 10.1159/000487702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Volume Overload and Current Techniques for the Assessment of Fluid Status in Patients with Renal Disease

Abstract: Volume overload is an important, may be the foremost, independent prognostic factor determining the outcome of hemodialysis patients. Therefore, it is crucial to measure fluid status of these patients and avoid volume overload. This review aims to evaluate volume overload, its effects on patients with renal diseases and current methodologies measuring volume status in the body. These techniques will be first classified as clinical evaluation and non-clinical and/or instrumental techniques, which includes bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 160 publications
(223 reference statements)
0
60
0
1
Order By: Relevance
“…Intense focus on fluid dynamics, including interdialytic fluid load, ultrafiltration intensity, and cardiovascular sequalae thereof, is probably needed [45]. Regardless of the intensity of HD, bioimpedance spectroscopy, lung ultrasonography, and pulmonary artery catheterization could be used to guide volume management [46].…”
Section: Resultsmentioning
confidence: 99%
“…Intense focus on fluid dynamics, including interdialytic fluid load, ultrafiltration intensity, and cardiovascular sequalae thereof, is probably needed [45]. Regardless of the intensity of HD, bioimpedance spectroscopy, lung ultrasonography, and pulmonary artery catheterization could be used to guide volume management [46].…”
Section: Resultsmentioning
confidence: 99%
“…The seriousness of hyperhydration is from long-time well known in ESKD patients [19], but more recently was also discussed in non-dialysis CKD. For example, Hung S-C et al found euvolemia in a little less than half (48%) from a cohort of 338 adults with stage 3 to 5 non-dialysis CKD [20], percentage which is very similar to our observations (52% patients with OH in normal range).…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, different ethnicities are not barriers to performing BIS measurement. In occurrence of bad data, fluid assessment should be guided by clinical assessment until a valid BIS measurement is obtained, and if conflicting results are found in BISmeasurement of haemodialysis patients, fluid assessment should always be guided by clinical assessment primarily, since evidence on the benefit of BIS is still scarce (Covic et al 2017;Ekinci et al 2018).…”
Section: Systematic Fluid Assessment In Haemodialysismentioning
confidence: 99%
“…; Ekinci et al . ). Evidence of the impact of BIS‐guided fluid management on survival is still lacking (Covic et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation